Formation of economic and legal measures for the development of the market of intellectual property objects - Maslak, Mariya; Pererva, Petro (Eastern-European Journal of Enterprise Technologies, 2023)
The problems of intellectual property market development have been investigated. It is proved that without the successful functioning of this market it is impossible to ensure the innovative development of the country. The characteristics of the intellectual property market, as well as the factors restraining its development, have been determined. The most important of them are significant volumes of outflow of Ukrainian scientists to foreign countries, low quality of Ukrainian patents, high level of counterfeiting and piracy, corruption pressure on the development and use of intellectual property, insufficient level of material support, etc. Therefore, the purpose of this study is to develop measures to strengthen the factors that contribute to the development of the intellectual property market and reduce the negative impact of factors on the Ukrainian technological market. To achieve the goal, it is proposed to introduce organizational and legal measures to improve the working conditions of employees of the main scientific institution of the country, the National Academy of Sciences (NAS) of Ukraine, the institutes of which produce most intellectual developments, as well as to form special financial and material mechanisms to support innovation at the expense of budget funds. Using the example of reforming the institutes of NAS, according to the proposed measures, proposals have been formed to preserve scientific personnel, intensify the cooperation of scientific institutions with business, built on the interest of all parties in the field of technology commercialization. Counteraction to counterfeiting is proposed to be carried out taking into account a more accurate calculation of the commercial risks to which business entities are exposed in the manufacture and use of innovations. It is recommended to strengthen the level of legal protection of exclusive rights. Legislative initiatives on the development of the intellectual property market have been formed, which relate to changes in patent legislation regarding utility models and bringing it to EU conditions